Pengaruh Model Pembelajaran Everyone Is A Teacher Here Berbantuan Media Padlet terhadap Hasil Belajar Teks Debat - Mawarni, Alfira Rara Sukma; Sumardi, Aida (Kajian Bahasa dan Sastra (KABASTRA), 2022)
The background of the thesis writing is the low learning outcomes of students in the Indonesian language subject matter of debate texts. The application of learning models and learning media that are not appropriate in learning results in low student learning outcomes. The purpose of this study was to determine the effect of the Everyone Is A Techer Here learning model assisted by the media padlet on the learning outcomes of debate texts at SMAN 12 Tangerang Selatan City, in class X MIPA 3 and X MIPA 4. The method used was quantitative with a nonequivalent control group research design. design. The results showed that there was an influence of the Everyone Is A Techer Here learning model assisted by the media padlet on the learning outcomes of the debate text. Based on the results of the experimental class hypothesis test obtained (t count ) -13.857 <0.05 (t table) 1.703, Based on these criteria that t count < t table then Ho is rejected and Ha is accepted. Based on the results of the control class hypothesis test obtained (t count ) -3.307 <0.05 (t table) 1.703 Based on these criteria that t count < t table then Ho is rejected and Ha is accepted, so it can be stated that there is a difference between the average value of the results overall control class student learning.